THE EFFECT OF THE CREATIVITY LEARNING MODEL ON NATURAL SCIENCE LEARNING OUTCOMES AND SELF EFFICACY - Ayu Ari Rahmayanti; I Gusti Ayu Tri Agustiana; Alexander Hamonangan Simamora (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
The research was conducted with the aim: (1) identify the effect of creativity learning model toward natural science subject’s learning outcomes and self-efficacy, (2) identify the effect of creativity learning model toward natural science subject’s learning outcomes, and (3) identify the effect of creativity learning model toward self-efficacy. This research was quasi-experimental research designed of Non-Equivalent Posttest Only Control Group. All fifth-grade classes of cluster I Buleleng district were the research population in total of 209 fifth-grade students from 8 schools. The research sample was determined through simple random sampling technique, obtained 2 schools in total of 59 students that was contained 29 students of SDN 1 Banyuning as the experiment class and 30 students of SDN 8 Banyuning as the control class. Essay test was used the research instrument to gather learning outcomes data, while questionnaire was used to measure self-efficacy. The data analysis was done descriptively to identify mean and standard deviation further tested through MANOVA test. The research findings portrayed: (1) simultaneously, creativity learning model effects in enhancing natural science subject’s learning outcomes and self-efficacy; (2) creativity learning model is able to improve natural science subject’s learning outcomes; and (3) creativity learning model is able to improve self-efficacy. Conclusively, creativity learning model presents has an influence on the aspects studies.